Hip Prognosis in Patients With Congenital Diastasis of the Pubic Symphysis. Issue 5 (18th May 2022) - Yamaguchi, Ryosuke; Nakamura, Tomoyuki; Yanagida, Haruhisa; Yamaguchi, Toru; Takamura, Kazuyuki; Wada, Akifusa; Nakashima, Yasuharu
Abstract : Background: Congenital diastasis of the pubic symphysis (CDPS) is a rare musculoskeletal malformation in the exstrophy-epispadias complex that is potentially associated with the development of hip dysplasia. The purpose of this study was to investigate the incidence and prognostic factors of hip dysplasia in patients with CDPS. Methods: Fifty-four hips in 27 patients with CDPS initially evaluated between 1983 and 2016 were retrospectively reviewed. The mean age at the first visit was 2.3 (0 to 8) years. The mean follow-up duration was 10.5 (1 to 36) years. Patient characteristics at the first visit, the clinical course at the most recent follow-up, and radiologic parameters on pubic malformation and hip dysplasia during at least 2 time points (first visit or age 1, and either the most recent visit or before hip surgery) were evaluated. Prognostic factors associated with the development of hip dysplasia were analyzed using univariate/multivariate analysis. The Kaplan-Meier survival curves were generated and compared based on these factors. Results: Nine of 27 patients (33%) and 13 of 54 hip joints (24%) with CDPS developed hip dysplasia. Paraplegia (odds ratio, 10.0; 95% confidence interval, 1.7-76.6) and center-edge angle of <5 degrees at the first visit or age 1 ( P <0.001) were independent predictors of the development of hip dysplasia. Patients with CDPS and either paraplegia or center-edge angle <5 degrees at the first visit or age 1 were significantly more likely to develop hip dysplasia than other patients (hazard ratio, 29.3; 95% confidence interval, 3.4-250). Conclusions: Approximately one third of patients with CDPS develop hip dysplasia. Paraplegia and center-edge angle of <5 degrees at the first visit are independent risk factors. Level of Evidence: Level III.